If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + 4x = (-91) 13 + 4x = -91 Solving 13 + 4x = -91 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 4x = -91 + -13 Combine like terms: 13 + -13 = 0 0 + 4x = -91 + -13 4x = -91 + -13 Combine like terms: -91 + -13 = -104 4x = -104 Divide each side by '4'. x = -26 Simplifying x = -26
| 20+(-52)= | | y-1=4/3(x-1) | | -y/13-2=1 | | -5y/3 | | 131+(3x-15)=180 | | (8/x)=(75/100) | | .5f+2.5=7.5 | | 33+6x=3(-x+9)-66 | | -5x=-92 | | 15-3x=4x+15 | | n/6-|-5|=11 | | 0.5(x+12)=15 | | -14u+10u-(-14)=6 | | 32-9=23 | | 0.5(18+12)=15 | | sin=3/4x-3=27 | | (5)(2b)-(5)(17)= | | f(x)=6x^4-5x^3-12x^2+5x+6 | | x+5x+4+x+2x-3x+6= | | 1x/2=3=6 | | 3/4x-3=27 | | 19.00+5.50x=11.00+6.75x | | 1/2x=3=6 | | 23x=-21 | | 2/5t=12/35 | | -4u-(-14)=6 | | m+14=8+2m | | 2x-5-8x=17 | | x-0.6=9.4 | | 9+(-9x)=-7 | | 5x+1=-5+10 | | 7K+2m=kr+4m+3fork |